Nizatidine for the treatment of patients with quetiapine-induced weight gain - Atmaca, M; Kuloglu, M; Tezcan, E; Ustundag, B; Kilic, N (Wiley, 2004)
It has been reported that nizatidine may reduce weight gain in schizophrenic patients on olanzapine treatment. Leptin has been reported to be associated with antipsychotic-induced weight gain. Thus, the purpose of the study was to evaluate whether nizatidine might be useful for the treatment of quetiapine-induced weight gain. Among the patients on the quetiapine monotherapy, 47 participated in the study for the two and half months of the open-label screening period. However, 28 patients who gained considerable weight in this period entered the 8-week, double-blind and placebo-controlled phase. These patients were randomly divided into two groups; quetiapine plus nizatidine (group I) and quetiapine plus placebo (group II) for the 8-week double-blind phase. The patients were evaluated at the baseline and at week 8 with respect to the positive and negative syndrome scale, body mass index, weight and serum leptin levels. The mean weight and leptin levels exhibited modest increases in both groups for the open-label screening period. In the double-blind period, in group 1, a minimal, but not statistically significant, decrease in weight was observed, with a mean of 1.0 +/- 0.6 kg. The weight increased in group II. The leptin levels decreased by a mean of 0.6 +/- 0.6 ng/ml in group I, and increased by 1.0 +/- 0.9 ng/ml in group II. At evaluation at week 8, a trend toward statistical significance in the mean serum leptin levels between groups was detected. The results suggest that nizatidine treatment may stop but not reduce the weight gain and is correlated with leptin levels in patients with schizophrenia on quetiapine treatment. Copyright (C) 2003 John Wiley Sons, Ltd.
Keywords: leptin; nizatidine; quetiapine; weight gain